2017
DOI: 10.1016/j.sjbs.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic composition and medicinal usage of Psidium guajava Linn.: Antifungal activity or inhibition of virulence?

Abstract: is a Myrtaceae plant whose medicinal properties are recognized in several locations. The use of teas and tinctures prepared from their leaves has been used to combat infections caused by fungi of the genus . In this study, aqueous extracts of leaves and hydroethanolic were tested to verify the antifungal potential and its chemical composition has been investigated. The microbiological assays were performed by broth microdilution to determine the minimum inhibitory concentration (MIC) and from these the minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 37 publications
1
21
0
2
Order By: Relevance
“…ex DC. And Psidium guajava L., the former having medicinal properties and is used to combat infections caused by fungi of the genus Candida [6,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ex DC. And Psidium guajava L., the former having medicinal properties and is used to combat infections caused by fungi of the genus Candida [6,27].…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the initial concentration of 16,384 µg/mL, the stock solution was diluted in sterile distilled water so that the DMSO concentration in the natural product had no activity in the cells tested. The reference antifungal was fluconazole (Capsule-FLUCOMED), diluted in sterile water at the same oil concentration [27]. For microbiological assays, two Candida albicans strains were used: CA INCQS 40006 (standard strain), obtained from the Oswaldo Cruz Culture Collection of the National Institute for Quality Control in Health (INCQS) and CA URM 4387 (clinical isolate), provided by mycology collection of the Federal University of Recife (URM -University Recife Mycology).…”
Section: Drugs Reagents Solution Preparation and Fungal Strainsmentioning
confidence: 99%
“…Virulence inhibition of Candida species has already been observed both by the action of extracts from other species belonging to the Myrtaceae family as well as by the action of plant products derived from other families. Morais-Braga et al (2016;2017) reported in their study that the aqueous and hydroethanolic extracts from Psidium guajava and Psidium brownianum (Myrtaceae) leaves affected the fungal virulence of C. albicans and C. tropicalis at the 16.384 μg/mL concentration. Brito et al (2015), showed that the C. krusei and C. tropicalis strains cultivated in culture medium in the presence of the Lippia sidoides (Verbenaceae) essential oil did not present pseudohyphae and hyphae at the 256 μg/mL concentration.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…The C. albicans was selected for association study, because, it is the most common pathogenic agent involved in systemic infections and the main strain responsible for infections caused by Candida fungi (Romani, 2012;Yapar, 2014). In previous studies, of our research group, with other species of this genus, P. brownianum and P. guajava extracts had their antifungal potential investigated, obtaining favorable results, where they also managed to affect the phenotypic plasticity of C. albicans and C. tropicalis, reducing the formation process of hyphae and pseudohyphae as their concentrations were increased (Morais- Braga et al, 2016bBraga et al, ,a, 2017. Candida albicans is a polymorphic fungus that can grow both in the yeast form (ovoid form), elongated ellipsoid cells with constrictions in the septa (pseudohyphae), or as true hyphae of parallel walls, as can be observed in Figure 2 -Growth Control (Berman, 2002).…”
Section: Discussionmentioning
confidence: 98%